Randomised controlled trial of lymphoblastoid interferon alfa in Europid men with chronic hepatitis B virus infection. Issue 6700 (9th September 1989) - Brook, M. G.; Chan, G.; Yap, I.; Karayiannis, P.; Lever, A. M.; Jacyna, M.; Main, J.; Thomas, H. C.
Abstract : OBJECTIVE--To confirm the findings of pilot studies that interferon alfa is an effective treatment of Europid men with chronic hepatitis B virus infection. DESIGN--Randomised controlled trial of three months treatment with interferon alfa followed by 12 months of observation. SETTING--Outpatient clinic of a tertiary referral centre. PATIENTS--37 Treated men (six anti-HIV positive) and 34 untreated men (nine anti-HIV positive) who met the criteria for the trial. Four controls failed to complete follow up. INTERVENTIONS--The treated group received subcutaneous injections of 5-10 MU interferon alfa/m2 daily for five days, then 10 MU/m2 thrice weekly for 11 weeks. Follow up continued at monthly intervals for 12 months. Untreated controls were monitored over the same period. MAIN OUTCOME MEASURE--Hepatitis B e antigen and hepatitis B virus DNA state after 15 months of observation. RESULTS--12 Of the 37 treated patients cleared hepatitis B e antigen and hepatitis B virus DNA, whereas only one of 30 untreated controls seroconverted over the same period--an increased response rate of 29% (95% confidence interval 13% to 45%). The life table estimate of response at 15 months was 35% in treated patients, an increase of 32% above controls (95% confidence interval 16% to 48%). The response rates in groups by predictive pretreatment variables were 12 of 31 anti-HIV negative patients (excess response 34%; 95% confidence interval 14% to 54%), 12 of 26 with chronic active hepatitis before treatment (excess response 46%; 27% to 65%), and 12 of 21 with a pretreatment serum aspartate aminotransferase activity greater than 70 IU/l (excess response 46%; 16% to 76%). The combination of these factors predicted response with a sensitivity of 100% and a specificity of 80%. Four of the 12 responders, who had all been infected for less than two years, also lost hepatitis B surface antigen. Treatment was well tolerated. CONCLUSIONS--Interferon alfa is effective in the treatment of a proportion of Europid men with chronic hepatitis B virus infection, who might be identified before treatment. Additional strategies are required to improve the rate of response.